Students’ Perceptions of Using Short English Videos in Learning Speaking At Grade 8 - Andhika Yudha Pratama Harahap; Fachri Yunanda; Bambang Nur Alamsyah Lubis (LPPPI Publishing, 2026)
This study investigates students’ perceptions of using short English videos in learning speaking at SMP Negeri 19 Medan. The research aims to explore how video-based learning is implemented and how it influences students’ speaking development. A qualitative descriptive approach was employed, involving eighth-grade students as participants. Data were collected through semi-structured interviews and classroom observations. The data analysis process included data reduction, data display, and conclusion drawing. The findings reveal that short English videos were effectively implemented as an engaging learning medium that enhanced students’ participation and reduced monotony in speaking activities. Students expressed positive perceptions toward the use of video, reporting increased motivation, improved pronunciation, better understanding of expressions, and greater confidence in speaking. However, several challenges were identified, including limited vocabulary, difficulty understanding fast speech, and comprehension problems. Despite these challenges, the study concludes that short English videos serve as an effective instructional medium in speaking learning when supported by appropriate material selection and teacher guidance.